Awareness and interest in biospecimen donation for cancer research: views from gatekeepers and prospective participants in the Latino community - Rodriguez, Elisa Marie (Springer Berlin Heidelberg, 2013)
Latinos are one of the fastest-growing population groups in the USA, and are underrepresented in scientific research and even more so in genetic research. The disproportionately lower number of certain subpopulations participating in biomedical research has a significant impact on the representativeness of scientific outcomes. We established a collaboration with scientists at a designated National Cancer Institute comprehensive cancer center to test the feasibility of community-based approaches for engaging Latinos in biospecimen donation for cancer genomic research. A methods triangulation approach was applied to gain a deeper understanding from the community, that included key informant interviews with Latino community leaders (N = 6), four focus groups (N = 22) with members of the Latino community, and the use of an audience response system within the focus groups to capture quantitative data. Overall, the majority of participants had never participated in biospecimen donation; however, despite being unaware of the biobank, they expressed willingness to participate as a way to help advance research. Themes included: Confusion on what biospecimen donation process entails; Barriers to and incentives for participation; Strategies and locations for reaching the Latino community. Clear communication of the “public good” as it relates to biospecimen donation by healthy/non-patient participants is a less clearly conceptualized message; yet, the significance of delivering this message is important to gaining participation and increasing the diversity of samples available for cancer genomic studies from a broader community context.